Heat Input Optimization for Reducing Floor Component Distortion Using FMEA - Idris Apandi; Setiawan Setiawan; Adi Rusdi Widya (Journal of Technology and Engineering, 2026)
Welding distortion is a major quality issue in heavy equipment fabrication because it affects dimensional accuracy, assembly efficiency, and production costs. This study aimed to identify the dominant causes of floor component distortion using Failure Mode and Effects Analysis (FMEA) and evaluate the effectiveness of heat input optimization in reducing distortion during the fabrication of Cool Body Truck units at PT ABC. A quantitative descriptive approach was employed using production quality records, field observations, dimensional measurements, interviews, and production documentation. Pareto analysis identified distortion as the most dominant production defect, accounting for approximately 42% of all recorded defects. FMEA results revealed that non-standardized welding parameters constituted the highest-priority failure mode, with a Risk Priority Number (RPN) of 432. Based on these findings, the welding current, voltage, and travel speed were optimized from 250 A, 28 V, and 250 mm/min to 230 A, 26 V, and 300 mm/min, respectively, reducing the heat input from 1,344 J/mm to 956.8 J/mm. Consequently, the average distortion decreased from 6 mm to 1 mm, satisfying the company's dimensional tolerance requirement of 2 mm. The findings demonstrate that integrating FMEA with heat input optimization effectively improves dimensional accuracy, minimizes rework, and enhances production efficiency in heavy equipment fabrication.